Sex Differences in Cardiac AMP-Activated Protein Kinase Following Exhaustive Exercise - Brown, Kevin D.; Waggy, Edward D.; Nair, Sreejayan; Robinson, Timothy J.; Schmitt, Emily E.; Bruns, Danielle R; Thomas, D.Paul (Sports Medicine International Open, 2020)
Ischemic heart disease presents with significant differences between sexes. Endurance exercise protects the heart against ischemic disease and also distinctly impacts male and female patients through unidentified mechanisms, though some evidence implicates 5′-AMP-activated protein kinase (AMPK). The purpose of this investigation was to assess the impact of training and sex on cardiac AMPK activation following exhaustive exercise. AMPK activation was measured in trained and sedentary mice of both sexes. Trained mice ran on a treadmill at progressively increasing speeds and duration for 12 weeks. Trained and sedentary mice of both sexes were euthanized immediately following exhaustive exercise and compared to sedentary controls. Endurance training elicited adaptations indicative of aerobic adaptation including higher max running velocities and cardiac hypertrophy with no differences between males and females. AMPK activity was higher in male compared to females, and trained exhibited higher AMPK activity compared to sedentary mice. In response to training, male mice activated AMPK more robustly than female mice. Chronic exercise training increases the ability to activate cardiac AMPK in response to exhaustive exercise in a sex-specific manner. Understanding the interaction between exercise and sex is vital for use of exercise as medicine for heart disease in both men and women.
Keywords: sex differences; cardiac; exercise; AMPK